Perancangan Simulasi Risk Pooling untuk Mendukung Proses Pembelajaran - Michael Gilbert Thimandalle; I Gede Agus Widyadana (Jurnal Titra, 2021)
This research was conducted to provide new innovations in the learning process activities of the Supply Chain Management course. By using simulation games, the learning process will run more interestingly so it is hoped that the knowledge taught can be absorbed by students optimally. The risk pooling material is one of many materials whose teaching will be more optimal with the existence of simulation games. This method compares the decentralized and centralized supply chain systems. In decentralized supply chain there are 3 stages and in centralized supply chain there are 2 stages. The simulation game was created using the AnyLogic application. The result of this research is in the form of a simulation game that describes a decentralized and centralized supply chain system.